A Close Look at Wealth Management Products from the Buyer’s Perspective: Evidence from China - Cao, June; Tu, G.Q. (Elsevier, 2022)
This study contributes to the shadow banking literature by investigating the determinants, market reactions, and consequences of wealth management products (WMPs) purchased by listed companies in China. The empirical results show that non-state-owned enterprises (non-SOEs) with a higher percentage of equity financing, more cash, higher profitability, larger total assets, lower sales growth, younger firm age, and lower Shanghai interbank offered rate (SHIBOR, which represents the overall availability of liquidity and credit in the economy) are more likely to buy WMPs. However, these factors largely fail to explain the WMP purchase behaviour of SOEs; in particular, compared to local SOEs, central SOEs are less likely to buy WMPs. We further find that the market reaction is significantly negative around the announcement of WMP purchases, and this finding is more pronounced for companies that have been listed for less than one year and are non-SOEs. Moreover, our results show that WMPs with longer maturity and larger amounts tend to have higher expected and real returns; in addition, SOEs are more likely to hold WMPs with longer maturity and have higher returns. This study is the first to investigate the determinants, market reactions, and consequences of WMP purchase behaviour in SOEs and non-SOEs, and it has implications for the financial assets held by non-financial firms. The results will be of interest to regulators, policymakers, and future academic research.